The Girl with the Bush Knife: Women, Adventure and the Tropics in Age of Consent and Nim’s Island - Allison Craven (eTropic: electronic journal of studies in the tropics, 2010)
Our paper broadly concerns the distinction of our cinematic heroines, Cora in Age of Consent (dir. Michael Powell 1969) and Nim of Nim’s Island (d. Mark Levin and Jennifer Flackett, 2008), from the more typical ‘bush women’ of Australian cinema and literature. The figure of our title, the ‘girl with the bush knife’, is a kind of marine creature, vividly captured in Age of Consent beneath tropical waters, mermaid-like but arguably a modified mermaid, while Nim of Nim’s Island is an androgynous child adventurer descended from a swag of male mariners, whose several accessories include a bush knife. Their appearances in films 40 years apart are as much the object of inquiry in this paper as the femininities they perform, in that these films also represent minor milestones in Australian cinema at points at which the film industry has undergone change. The contexts of these changes are somehow signified, we suggest, by the use of tropical locations and settings, and we are therefore drawing attention to the way these female characters are accompanied by the spectacle of the tropical place in its difference from the more mythologised bush and desert landscapes of Australian mise-en-scene. Indeed, both Age of Consent and Nim’s Island use locations in Queensland to fictionalize settings that are either in or towards Queensland, and both adapt the well established symbology of Eden, paradise and epic journey, that are defined in studies of Queensland in film and television by Bruce Molloy (1990) and Albert Moran (2001). But whereas Molloy and Moran largely concentrate on films produced by Australian interests within the ambit of a local film industry, our films are both instances of films made by international interests, with a degree of local involvement and capital, on visitations to ‘locations less used’, namely North and Far North Queensland.